Art Perception in the Museum: How We Spend Time and Space in Art Exhibitions - Claus-Christian Carbon (i-Perception, 2017)
Aesthetics research aiming at understanding art experience is an emerging field; however, most research is conducted in labs without access to real artworks, without the social context of a museum and without the presence of other persons. The present article replicates and complements key findings of art perception in museum contexts. When observing museum visitors ( N  = 225; 126 female, M (age) = 43.3 years) while perceiving a series of six Gerhard Richter paintings of various sizes (0.26–3.20 sq. m) in a temporary art exhibition in January and February 2015 showing 28 paintings in total, we revealed patterns compatible to previous research. The mean time taken in viewing artworks was much longer than was mostly realized in lab contexts, here 32.9 s ( Mdn  = 25.4 s). We were also able to replicate visitors spending more time on viewing artworks when attending in groups of people. Additionally, we uncovered a close positive relationship ( r 2  = .929) between canvas size and viewing distance, ranging on average between 1.49 and 2.12 m ( M  = 1.72 m). We also found that more than half of the visitors returned to paintings, especially those people who had not previously paid too much attention at the initial viewing. After adding the times of returning viewers, each picture was viewed longer than had been estimated in previous research ( M  = 50.5 s, Mdn  = 43.0 s). Results are discussed in the context of current art perception theories, focusing on the need for the ecologically valid testing of artworks in aesthetics research.